2019
DOI: 10.1136/bcr-2018-225947
|View full text |Cite
|
Sign up to set email alerts
|

Non-infectious aortic and mitral valve vegetations in a patient with eosinophilic granulomatosis with polyangiitis

Abstract: Eosinophilic granulomatosis with polyangiitis (EGPA) is a rare form of vasculitis characterised by atopic manifestations, inflammation of small-sized to medium-sized arteries and veins, hypereosinophilia and tissue infiltration with eosinophils. Cardiac complications occur most commonly in the absence of antineutrophil cytoplasmic antibodies. Cardiac complications include coronary arteritis (rare), pericarditis, myocarditis, endocardial fibrosis (Loeffler’s endocarditis) and intracavitary thrombosis of the lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…While EGPA itself is a rare disease, non-infectious vegetations have been documented in multiple cases. In a case report of a large non-infectious valvular vegetation associated with EGPA, they report cardiac complications in 50-62% of patients, most commonly in ANCA-negative cases [ 9 ]. According to Goodfield, cardiac involvement is not as rare as initially presumed, present in ≤ 44% of cases of EGPA [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…While EGPA itself is a rare disease, non-infectious vegetations have been documented in multiple cases. In a case report of a large non-infectious valvular vegetation associated with EGPA, they report cardiac complications in 50-62% of patients, most commonly in ANCA-negative cases [ 9 ]. According to Goodfield, cardiac involvement is not as rare as initially presumed, present in ≤ 44% of cases of EGPA [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pilania et al (7) also reported that pulmonary arterial hypertension is a rare occurrence in ANCA-associated vasculitis. Löffler endocarditis of HES or EGPA progresses through three stages, namely acute necrotic stage (infiltration of eosinophils in the myocardium), thrombotic stage (mural thrombi formation along the damaged endocardium), and fibrotic stage (the granulation tissue changing into hyaline fibrosis), which may overlap (2,8). Myocardial fibrosis may develop rapidly and immediate aggressive treatment may help to slow the progression of chronic heart failure (8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…Löffler endocarditis of HES or EGPA progresses through three stages, namely acute necrotic stage (infiltration of eosinophils in the myocardium), thrombotic stage (mural thrombi formation along the damaged endocardium), and fibrotic stage (the granulation tissue changing into hyaline fibrosis), which may overlap (2,8). Myocardial fibrosis may develop rapidly and immediate aggressive treatment may help to slow the progression of chronic heart failure (8)(9)(10). Right-sided heart failure can be a consequence of left ventricular dysfunction; however, Fitchett et al (11) believed that right ventricular failure might in certain circumstances develop either before or after left ventricular failure when there is a diffuse myocardial disease.…”
Section: Discussionmentioning
confidence: 99%
“…Генетическая предрасположенность к эндокардитам привлекает внимание ученых и клиницистов [6][7][8]; имеются данные об ассоциации однонуклеотидных полиморфизмов в генах гемостаза и фолатного цикла с синдромом вегетаций на клапанном аппарате сердца [9]. На выборке 123 пациентов с инфекционным эндокардитом (ИЭ) показана ассоциация более высокого риска ИЭ с генотипом ТТ полиморфизма rs1205 в гене CRP, а снижение риска ИЭ обусловлено генотипом GA полиморфизма rs1143634 гена IL1B, генотипом GT полиморфизма rs3212227 гена IL12B, генотипом АС полиморфизма rs1130864 гена CRP и G-аллелью полиморфизма rs1801197 гена CALCR [10].…”
Section: Introductionunclassified